A population pharmacokinetic‐pharmacodynamic model of YH12852, a highly selective 5‐hydroxytryptamine 4 receptor agonist, in healthy subjects and patients with functional constipation - Siun Kim; Hyun A. Lee; Seong Bok Jang; Howard Lee (Wiley, 2021)
Abstract YH12852, a novel, highly selective 5‐hydroxytryptamine 4 (5‐HT4) receptor agonist, is currently under development to treat patients with functional constipation. In this study, we aimed to develop a pharmacokinetic (PK)-pharmacodynamic (PD) model that adequately described the time courses of the plasma concentrations of YH12852 and its prokinetic effect as assessed by the Gastric Emptying Breath Test (GEBT) and to predict the prokinetic effect of YH12852 at higher doses through PD simulation. We used the plasma concentrations of YH12852 from patients with functional constipation and healthy subjects and the GEBT results from healthy subjects obtained from a phase I/IIa trial. The PK‐PD modeling and covariate analysis were performed using NONMEM software. The prokinetic effect of YH12852 was described using a semimechanistic multicompartment PD model and an empirical model by Ghoos et al. A two‐compartment model with first‐order absorption adequately described the observed concentration‐time profiles of YH12852. The semimechanistic multicompartment PD model and the revised Ghoos model with two slope parameters adequately described the observed kPCDt (the percent dose of 13C excreted in the exhaled air at minute t after completing the test meal, multiplied by 1000) values. YH12852 accelerated gastric emptying even at low doses of 0.05-0.1 mg, and its prokinetic effect was greater in subjects suffering from more severe functional constipation. The PD simulation experiments revealed that the change from baseline in the half time for gastric emptying induced by YH12852 increased in a dose‐dependent manner at 0.05-5 mg although the results at doses >0.1 mg were extrapolated. We also showed that the empirical Ghoos model is a special case of the general semimechanistic multicompartment PD model for gastric emptying.